Early Ordovician brachiopods from south-west Wales. Issue 6 (December 2019) - Cocks, L. Robin M.; Popov, Leonid E.
Abstract: The Early Ordovician brachiopods of south-west Wales (Pembrokeshire and Carmarthenshire) are identified, in most cases for the first time. That period is termed the local Arenig Stage in Britain, but it is now correlated with the Floian, Dapingian, and earlier half of the Darriwilian, which are more recently established international stages in the system of stratigraphical nomenclature. The rocks in south-west Wales were laid down as turbidites in a backarc basin which formed part of the margin of the relatively small independent microcontinent of Avalonia at that time. However, since the Rheic Ocean between Avalonia and the immense Gondwana continent was relatively narrow in the Arenig, the brachiopods reviewed here can be established to be part of the Mediterranean Province, which was also extensive in the higher-latitude sectors in and around Gondwana in the Early Ordovician. The 17 brachiopod species identified within the Arenig brachiopod faunas of south-west Wales are described, including the new species Aporthophyla prisca, Tritoechia bolohaulensis, Skenidoides pontyfennensis and Paurorthis? llangynogensis.